Laboratory dynamic accuracy evaluation method and system verification for gravity gradiometer - Da Li; Chengsuo Li; Wei Gao; Zishan Zhang; Li Wu; Zhong Li (地震科学进展)
To meet the demand for reliably evaluating the measurement accuracy of the gravity gradiometer under dynamic conditions, a method for dynamically assessing the accuracy of the gravity gradiometer in a laboratory setting was proposed. Firstly, a method for creating an environment of approximately uniform gravity gradient was introduced. It involved the symmetric distribution of rectangular mass bodies within a localized spatial range to generate an approximately uniform gravity gradient excitation, with an excitation magnitude reaching 62.4 E and non-uniformity better than 1.3 E. Secondly, an evaluation criterion was proposed based on the gravity gradiometer’s sensitivity to gravity gradient excitation produced by the movement of mass bodies under dynamic laboratory conditions, leading to the proposal of a method for evaluating the dynamic accuracy of the gravity gradiometer in the laboratory. Finally, a laboratory dynamic accuracy evaluation system for the gravity gradiometer was established using a gravity gradient excitation device and a six-degree-of-freedom motion simulation platform. Validation experiments were conducted in the laboratory using a self-developed gravity gradiometer. The experimental results indicate that this evaluation system is capable of assessing the dynamic measurement accuracy of the gravity gradiometer in the laboratory, meeting the evaluation requirements for domestically developed dynamic gravity gradiometers.